Profil dan Keragaman Ayam Kub yang Dipelihara Oleh RTM Peternak dalam Program Bekerja di Kabupaten Indramayu: Profile and Diversity of KUB Chicken Raised by Farmer Households in Bekerja Program in Indramayu District - Ganjar Hadiyanto Pratomo (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2021)
Abstract The aim of this study was to determine the diversity of KUB chickens raised by farmer households in Indramayu Regency in the implementation of the 2019 BEKERJA program. The BEKERJA program is carried out in 8.189 farmer households by providing 50 DOC, chicken feed during 5 weeks, maintenance support facilities include feed tray, drinking bottles, brooder cages, cables, lights, and cage subsidy for 4 weeks chickens. The parameters observed were the number of chicken mortality, age of first egg laying and the number of egg production for the first time. The observations showed that the mortality of KUB chickens increased at 3 months of raised, which was caused by the sale and slaughter of chickens and the mortality of chickens due to improper raise management. Hens that lay eggs early in the District of Anjatan and District of Bongas 7.066 and 1.041, respectively. The results of the study showed that there was diversity at the beginning of egg-laying chicken due to improper feeding management, but KUB chicken had the potential to be developed as an egg and meat producer in Indramayu Regency. Keywords: BEKERJA Program; Diversity at the beginning of egg-laying chicken; KUB chicken Abstrak Kajian bertujuan untuk mengetahui keragaman ayam KUB yang dipelihara oleh RTM di Kabupaten Indramayu dalam pelaksanaan program BEKERJA tahun 2019. Program BEKERJA melibatkan 8.189 RTM dengan memberikan bantuan 50 ekor DOC ayam KUB, pakan selama 5 minggu pemeliharaan, bantuan sarana prasarana pemeliharaan meliputi tray tempat pakan, botol tempat minum, kandang brooder, kabel, lampu, dan bantuan subsidi kandang untuk ayam umur 4 minggu. Parameter yang diamati adalah jumlah kematian ayam, umur bertelur pertama kali dan produksi telur pertama kali. Hasil pengamatan menunjukkan bahwa kematian ayam KUB meningkat pada 3 bulan usia pemeliharaan, yang disebabkan oleh penjualan dan pemotongan ayam serta kematian akibat manajemen pemeliharaan yang kurang tepat. Jumlah produksi telur pertama kali di Kecamatan Anjatan dan Kecamatan Bongas masing-masing sebesar 7.066 butir dan 1.041 butir. Hasil kajian menunjukkan adanya keragaman pada awal bertelur ayam yang diakibatkan oleh manajemen pemberian pakan yang tidak tepat, namun ayam KUB berpotensi dikembangkan sebagai penghasil telur dan daging di kabupaten Indramayu Kata kunci : Ayam KUB; Keragaman awal bertelur; Program BEKERJA